Determining the fatigue parameters in total strain life equation of a material based on monotonic tensile mechanical properties. (1st March 2020) - Yang, Shun; Yang, Long; Wang, Yanrong
Highlights: A new fatigue life prediction method has been proposed and obtained satisfied life prediction results for various of typical aero-engine materials. Abstract: This paper summarized and evaluated a variety of low-cycle fatigue life estimation methods and gives the expression of fatigue strength coefficient, fatigue ductility coefficient, fatigue strength exponent, fatigue ductility exponent, successfully established the relationship among four parameters in total strain life equation and monotonic tensile parameters such as Young's module, ultimate stress, yield stress, reduction in area, elongation. Therefore a new fatigue life prediction method has been proposed, with which various materials' fatigue life have been predicted and acquired satisfied life prediction results. The influence of fatigue parameters in the total strain life equation on fatigue life prediction results has been evaluated and in the mid-high (10 4 –10 6 ) life stage, fatigue life is very sensitive to the true fracture stress, if the stress is reduced by 5%, the fatigue life will be increased by about 50%. The Material's Low-Cycle Fatigue Life Prediction System (the MLCFLPS) has been developed based on the Visual Basic which can evaluate parameters in total strain life equation more convenient and fast, which shows strong mechanical significance in life prediction of engineering structures.